Simultaneous approximation of modulus and values of Jacobi elliptic functions (in Ukrainian) - Ya. M. Kholyavka (Математичні Студії)
Let $sn_i z$ be algebraically independent Jacobi ellipticfunctions, $(4K_i,2iK'_i)$ be main periods and $gk_1,, gk_2$be their moduli $sn_i z$ ($iin{1,2}$). We estimate from below thesimultaneous appro-xi-ma-tion $gk_1,, gk_2,,sn_1K_2,,sn_2i K'_1$.